PRESERVING CULTURE AND REVIVING ANCESTRAL HERITAGE THROUGH HISTORICAL STUDIES AND LIVE ACTION VIDEO PRODUCTION OF KEBO-KEBOAN BANYUWANGI - Sivfian Hendra Legowo; Sahru Romadloni; Ach. Ridlo Ilwafa (SOSIOEDUKASI, 2026)
This study aims to reconstruct the local history of the Kebo-Keboan tradition in Alasmalang Village, map its values, symbols, and socio-cultural functions, and design a research-based live action video production as a preservation education medium. The method used is descriptive qualitative with a historical approach through the stages of heuristics, source criticism, interpretation, and historiography; data were collected through observation, in-depth interviews with the Traditional Leader (Doni Agus Fergianto/Mbah Doni), ritual figure Mbah Ribut, and Village Head Abdul Munir, accompanied by documentation and document studies. The results show that Kebo-Keboan is rooted in the memory of crisis (pagebluk) and the legitimacy of sacred spaces (Watu Loso and cornerstones), developing through a period of formation, organizational strengthening, and a modern phase marked by audience expansion, packaging adjustments, and the need for representational control. The conclusion of the study confirms that the integration of historical studies and community-validated live action video production can broaden access to understanding for the younger generation without shifting the community's cultural authority. The limitations of the study lie in the dominance of oral sources and the lack of a long-term media impact evaluation.